2015
DOI: 10.1007/s11103-015-0301-6
|View full text |Cite
|
Sign up to set email alerts
|

Expression of SOD and APX genes positively regulates secondary cell wall biosynthesis and promotes plant growth and yield in Arabidopsis under salt stress

Abstract: Abiotic stresses cause accumulation of reactive oxygen species (ROS), such as hydrogen peroxide (H2O2) in plants. Sophisticated mechanisms are required to maintain optimum level of H2O2 that acts as signalling molecule regulating adaptive response to salt stress. CuZn-superoxide dismutase (CuZn-SOD) and ascorbate peroxidase (APX) constitute first line of defence against oxidative stress. In the present study, PaSOD and RaAPX genes from Potentilla atrosanguinea and Rheum australe, respectively were overexpresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(97 citation statements)
references
References 61 publications
4
92
0
1
Order By: Relevance
“…The triggering of physiological metabolism and enhanced defense enzymes in eggplant upon treatment with RGS also indicates a priming phenomenon for yield production, as previously shown in cabbages [55]. Moreover, overproduction of SOD has been reported as a plant growth promoter under salt stress conditions [56]. These reports are strongly coherent with our present study.…”
Section: Rgs As An Antioxidative Defense Regulatorsupporting
confidence: 92%
“…The triggering of physiological metabolism and enhanced defense enzymes in eggplant upon treatment with RGS also indicates a priming phenomenon for yield production, as previously shown in cabbages [55]. Moreover, overproduction of SOD has been reported as a plant growth promoter under salt stress conditions [56]. These reports are strongly coherent with our present study.…”
Section: Rgs As An Antioxidative Defense Regulatorsupporting
confidence: 92%
“…Several studies have shown that lignin accumulation and high levels of lignin biosynthetic gene expression are important for abiotic stress tolerance (Hu et al, 2009;Shafi et al, 2015;Srivastava et al, 2015). In this study, heavier deposition of lignin was observed specifically in the secondary xylem and phloem fibers of BpNAC012-OE transgenic plants under salt and osmotic stress conditions, which was consistent with the results that BpNAC012 highly induced the expression of lignin biosynthetic genes in response to abiotic stress treatments.…”
Section: Overexpression Of Bpnac012 Induces Enhanced Lignification Agsupporting
confidence: 91%
“…The number of lignified cells in vascular bundles was distinctly greater in plants under salt stress, with maximum expansion of the lignified area found in the root vasculature (S anchez-Aguayo et al, 2004). The expression levels of several key genes involved in the lignin biosynthesis pathway were altered upon salt treatment (Shafi et al, 2015). The increased expression of these proteins might help reduce the bypass water flow that allows Na + ions to enter roots via an apoplastic pathway.…”
Section: Discussionmentioning
confidence: 99%